Stock market integration and its implications for international trade, exchange rates and interest rates in ASEAN-5 countries - Saeedi, Mitra (2014)
This research investigates the linear and asymmetric cointegration among the stock markets of ASEAN-5 (Association of Southeast Asian Nations, the five original member countries namely Malaysia, Indonesia, Singapore, the Philippines, and Thailand) and those of Europe, Japan, and the United States. Diversification plays an important role in the investment decision. Having the knowledge of the interdependence and integration of stock markets, investors try to diversify their assets internationally as long as the returns of the stocks in their portfolio from different markets are less than perfectly correlated with the national market. Testing for the asymmetric cointegration prevents problems that may result in misleading inference in symmetric cointegration test which ignores the intrinsic nonlinearities. This study is the first to examine the existence of asymmetric cointegration among the stock markets. It also contributes to the prior research by examining the importance of trade in explaining the interdependence among the stock markets of interest (trade relation hypothesis) and the possible long run and short run relationship among the two important monetary macroeconomic factors, interest rates and exchange rates, and the stock prices of ASEAN-5. The empirical analysis applies Autoregressive Distributed Lag and Asymmetric Autoregressive Distributed Lag cointegration tests over the period of 1990 to 2010. The results show no evidence of linear or asymmetric long run relationship among the stock markets. The Granger causality approach shows that the causality runs from European stock market to the stock markets of Indonesia and Thailand. Therefore, according to the results, there is a potential opportunity of portfolio diversification for the investors and portfolio managers from the major developed markets in the long run. The generalized variance decompositions and the correlation test with bootstrap procedure are employed to test the trade relation hypothesis. Based on the findings, the trade relation hypothesis fails to be a general rule in ASEAN-5 countries. Being segmented from the major developed markets, ASEAN-5 countries are examined for the possible long run and short run effects of local macroeconomic factors so the policy makers can adopt proper monetary policy to boost up their stock market performance attracting more international funds. Collectively, the results show no long run relationship among the interest rates and exchange rates and stock prices in ASEAN-5; however, from the generalized impulse response functions immediate and quick negative responses of the ASEAN-5 stock markets to innovations in the interest rates and exchange rates are felt. The findings of the study carry important implications for Policymakers, investors, portfolio managers, and scholars interested in ASEAN-5.